Effectiveness Of Oxytocin Massage In Increasing Breast Milk Production - Satiyem, Satiyem; Murtiningsih, Dewi (Jurnal Medika Malahayati, 2024)
One of the reasons why breastfeeding problems are caused by breast milk not coming out is because the mother is less willing to give her breast milk, some families even suggest giving formula milk as a substitute for breast milk. Postpartum mothers and their families do not know that there is a way to express breast milk quickly and can increase breast milk production, one of which is by doing oxytocin massage. This oxytocin massage method can stimulate the breasts to increase the production and smooth flow of breast milk. Subject and method: Respondents from breastfeeding mothers at PMB Yuni Wazaituni Sukoharjo. Total sampling technique for taking respondents. The number of respondents was 32 people. Quantitative research using a Quasi Experimental method research design. Results: There was an effect of giving oxytocin massage on breast milk production in PMB Yuni Wazaituni Sukoharjo, both in the treatment group with a p value of 0.000 (<0.05) and the control group with a p value of 0.000 (<0.05). There is a difference in the effect of the effectiveness of oxytocin massage on breast milk production in breastfeeding mothers in the treatment group and the control group with a p value of 0.020.